STRATEGI BANK SYARIAH INDONESIA KC MAKASSAR VETERAN DALAM MEREKRUT NASABAH CALON JAMAAH HAJI DI KOTA MAKASSAR 2021 (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This study discusses how the Strategy of Bank Syariah Indonesia KC Makassar Veterans in Recruiting Prospective Customers of Hajj Pilgrims in Makassar City 2021. This study aims to find out how the strategy of BSI KC Makassar Veterans in recruiting prospective Hajj pilgrims in Makassar City, opportunities and obstacles to the BSI KC strategy Makassar Veterans in recruiting prospective Hajj pilgrims in Makassar City, the response of prospective Hajj pilgrims to the strategy of BSI Makassar Veterans Branch in Makassar City?This study uses qualitative research with a management approach to Hajj and Umrah. Methods of collecting data through interviews, observation, documentation, online searches, and library studies. Technical data analysis is data collection, data reduction, data presentation and verification or drawing conclusions.The results of this study indicate that the strategy undertaken by PT. Bank Syariah Indonesia, Tbk in this case BSI KC Makassar Veteran is the marketing mix or commonly known as the Marketing Mix with seven variables (7P) including Product, Price, Place, Promotion ), People (People), Physical Environment (Physical Events) and Process (Process). The products offered by BSI KC Makassar Veterans are Easy Savings, TabunganKu, BSI Giro, Pension Savings and Mabrur Savings. Likewise, the services offered are BSI Mobile, BSI Net Banking, BSI Notifications and BSI Call. Product pricing is adjusted to market prices and local government policies. Promotions carried out by BSI KC Makassar Veterans are in collaboration with PIHK and BPIU, visits to Islamic schools, advertising and publicity. The service applied is polite, courteous, friendly, greeting, smiling, and good body language.The implication of this research is that PT. Bank Syariah Indonesia, Tbk especially BSI KC Makassar Veterans should be more active to carry out updates or innovations in marketing activities, both promotion and socialization, so that information about this Bank can be spread quickly. Moreover, PT. Bank Syariah Indonesia, Tbk is a newcomer bank in the world of bank financial institutions. In addition, BSI KC Makassar Veterans must also maintain optimal service.